Participatory video: climate change in Nicaragua - International Center for Tropical Agriculture (2014)
This participatory video was made by fifteen young Nicaraguan farmers. Through this video they want to communicate their message: “we need to take care of our ecosystem”. They have interviewed various community-members concerning this topic and they explain how they see climate change affecting their daily lives, and the practices they undertake to adapt and mitigate. May 2014, Somotillo, Nicaragua.